Studying the Self-Cleaning Ability of Water Bodies and Watercounts of Arshalyn District of Akmola Region - AKBAYEVA, Lyailya; MAMYTOVA, Nurgul; BEISENOVA, Raikhan; TAZITDINOVA, Rumiya; ABZHALELOV, Akhan; AKHAYEVA, Ainur (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020DO - 10.14505//jemt.v11.5(45).07, 2020)
In this paper, the self-purification potential of water bodies and watercourses in the Arshalinsky district was studied in an administrative unit of the Akmola region: Bolshaya Saryoba, Malaya Saryoba, Zhaltyrkol (Arhaniya), Koigeldy, Zhangula, and a section of the Yesil River. The self-cleaning ability of water bodies was assessed by such oxygen indicators as the amount of dissolved oxygen and BOD5. In water samples from water bodies, the dominant phytoplankton and zooplankton species were identified as possible agents or indicators of the self-purification capacity of water bodies. The task of the work was to identify the relationship of self-cleaning ability with inorganic pollution, saprobity.